Hearing Loss in Id1−/−; Id3+/− and Id1+/−; Id3−/− Mice Is Associated With a High Incidence of Middle Ear Infection (Otitis Media) - Zheng, Qingyin; Zheng, Tihua; Zhang, Aizhen; Yan, Bin; Li, Bo; Zhang, Zhaoqiang; Zhang, Yan (Frontiers in Genetics, 2021)
Id proteins are crucial for inner ear development but whether Id mutations affect middle ear function is not known. In this study, we obtained Id1-/-; Id3+/- as well as Id1+/-; Id3-/- mice and carefully examined the middle ear morphology as well as auditory function. Our study showed that there is a high incidence (>80%) of middle ear infection in the compound mutant mice. These mutant mice showed hearing impairment starting around 30 days of age, as the mutant mice presented elevated auditory brainstem response (ABR) thresholds compared to those of the littermate controls. Distortion product of otoacoustic emission (DPOAE) was also used to evaluate the conductive function of the middle ear, and we showed much lower DPOAE amplitudes in the mutant mice, suggesting sound transduction in the mutant middle ear is compromised. This is the first study of middle ear of the Id compound mutant mice, and high incidence of middle ear infection determined by otoscopy and histological analysis of middle ear suggest ID1/ID3 compound mutant mice are a novel model for human otitis media.